Raman Spectroscopy: Guiding Light for the Extracellular Matrix - Bergholt, Mads S.; Serio, Andrea; Albro, Michael B. (Frontiers in Bioengineering and Biotechnology, 2019)
The extracellular matrix (ECM) consists of a mesh of fibrous proteins, glycoproteins, polysaccharides and proteoglycans, and is essential for maintaining tissue integrity and function. Imaging and biomolecular characterization of the ECM is critical for understanding disease onset and the progression and development of novel disease-modifying therapeutics. Recently, there has been an increasing interest in the use of Raman spectroscopic imaging to characterize the ECM. Raman spectroscopy is a label-free vibrational technique that offers unique insights into the structure and composition of tissues and cells at the molecular level. This technique can be applied across a broad range of ECM imaging applications, including in vitro, ex vivo, and in vivo analysis. State-of-the-art confocal Raman imaging now enables label-free assessments of the ECM structure and composition with high biomolecular contrast. Further, using novel fiber-optic instrumentation, it is possible to perform in vivo measurements of human tissue across a broad range of organs. A palette of advanced computational methods based on multivariate statistics, spectral unmixing and machine learning are the key tools for extracting specific biochemical information from the ECM. Here, we review Raman imaging techniques and applications for ECM characterizations over a range of tissue systems. We further discuss the challenges in the widespread adoption of Raman imaging in biomedicine as an exploratory tool for ECM characterization. The results of the latest discovery-driven Raman imaging studies are summarized spanning from regenerative medicine, cartilage/hard tissues and cardiovascular to cancers, illustrating both current and potential future applications in biomedicine.